Evolving Tale of TCPs: New Paradigms and Old Lacunae - Dhaka, Namrata; Bhardwaj, Vasudha; Sharma, Manoj K.; Sharma, Rita (Frontiers in Plant Science, 2017)
TCP genes are key mediators of genetic innovations underlying morphological novelties, stress adaptation and evolution of immune response in plants. They have a remarkable ability to integrate and translate diverse endogenous, and environmental signals with high fidelity. Compilation of studies aimed at elucidating the mechanism of TCP functions shows that it takes an amalgamation and interplay of several different factors, regulatory processes and pathways, instead of individual components, to achieve the incredible functional diversity and specificity, demonstrated by TCP proteins. Through this minireview, we provide a brief description of key structural features and molecular components, known so far, that operate this conglomerate, and highlight the important conceptual challenges and lacunae in TCP research.